Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Nanocomposites of polypropylene impact copolymer and organoclays: role of compatibilizers - Deenadayalan, E.; Vidhate, Shailesh; Lele, Ashish K. (Polymer International, 2006)
Nanocomposites of polypropylene impact copolymer and organoclays were prepared using different compatibilizers (polypropylene-graft-(maleic anhydride) (PPMA), polyethylene-graft-(maleic anhydride) (PEMA) and their mixture) and varying percentages of clay (3 and 6%) in an attempt to obtain balanced mechanical properties. The nanocomposites were prepared by melt compounding and test specimens were prepared by injection molding. Mechanical properties such as tensile, flexural and Izod impact strength are reported. The clay dispersion was investigated using wide-angle X-ray diffraction while the phase morphology was characterized using scanning electron microscopy. It is shown that the mechanical properties of the system with mixed PPMA and PEMA compatibilizers showed the best balance of mechanical properties among the nanocomposites explored. (C) 2006 Society of Chemical Industry.
Keywords: clay; compatibilizers; Nanocomposites; polypropylene

Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization

Development of nanofibrous morphology in LDPE/LLDPE/PP blends and its effect on mechanical properties of blend films - Sonawane, Pradip S.; Radhakrishnan, S.; Bhangale, J. A.; Gadhavi, A. L.; Khare, Anagha (Journal of Applied Polymer Science, 2008)
Nanofibrous morphology has been observed in ternary blends of low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and isotactic polypropylene (PP) when these were melt-extruded via slit die followed by hot stretching. The morphology was dependent on the concentration of the component polymers in ternary blend LDPE/LLDPE/PP. The films were characterized by wide angle X-ray diffraction (XRD), scanning electron microscopy (SEM), and testing of mechanical properties. The XRD patterns reveal that the P phase of PP is obtained in the as-stretched nanofibrillar composites, whose concentration decreases with the increase of LLDPE concentration. The presence of PP nanofibrils shows significant nucleation ability for crystallization of LDPE/LLDPE blend. The SEM observations of etched samples show an isotropic blend of LDPE and LLDPE reinforced with more or less randomly distributed and well-defined nanofibrils of PP, which were generated in situ. The tensile modulus and strength of LDPE/LLDPE/PP blends were significantly enhanced in the machine direction than in the transverse direction with increasing LLDPE concentration. The ultimate elongation increased with increasing LLDPE concentration, and there was a critical LLDPE concentration above which it increased considerably. There was a dramatic increase in the falling dart impact strength for films obtained by blow extrusion of these blends. These impressive mechanical properties of extruded samples can be explained on the basis of the formation of PP nanofibrils with high aspect ratio (at least 10), which imparted reinforcement to the LDPE/LLDPE blend. (C) 2007 Wiley Periodicals, Inc.
Keywords: linear low density polyethylene; low density polyethylene; mechanical properties; melt-extruded films; nanofibrous morphology; polypropylene; ternary blends

Effect of gamma-dose rate on crystallinity and morphological changes of gamma-sterilized biomedical polypropylene - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2009)
The present work is aimed to study the changes in crystallinity and morphology of biomedical polyolefins after gamma-sterilization. The isotactic polypropylene (iPP) films were sterilized by gamma-radiation and the changes were characterized by differential scanning calorimetry (DSC), wide angle X-ray diffraction (WAXD) and atomic force microscopy (AFM) techniques. The effect of dose rate on crystallinity changes also was focused. It was found that crystallinity and morphology significantly changed with gamma-irradiation. There was an increase in crystallinity Lip to 10 kGy accompanied with decrease in viscosity and mechanical properties. The changes in crystallinity mainly depend on gamma-irradiation dose and dose rate. The rise in crystallinity was attributed to chain scission and forming new perfect lamellae. However, the reduction was accompanied by occurrence of gamma- and beta-phases and crosslinking. Possible explanations for transitions in phases are also discussed based on our results. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crystallinity; Dose rate; Gamma radiation; mechanical properties; Morphology; polypropylene

Exfoliation of clay layers in polypropylene matrix using potassium succinate-g-polypropylene as compatibilizer - Rama, Mallikarjuna Shroff; Neppalli, Ramesh; Chellaswamy, Ramesh; Swaminathan, Sivaram (Composites Science and Technology, 2010)
The efficiency of potassium succinate-g-polypropylene (KPPSA) as compatibilizer for the dispersion of clay in a high molecular weight polypropylene during melt mixing for the preparation of nanocomposites was evaluated and compared with maleic anhydride-g-polypropylene (PPMA). Nanocomposites were prepared by direct melt mixing and by masterbatch methods and the structure obtained was characterized by WAXD and TEM. The exfoliation and better dispersion of the organoclay was observed with KPPSA than PPMA. The dispersion of clay was found to be dependent on the method of preparation, type and the amount of compatibilizer used. The dispersion was better when the nanocomposites were prepared by two step masterbatch route than the single step direct mixing method. Flexural moduli and crystallization behavior were studied and correlated with the dispersion of organoclay in the PP matrix. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: differential scanning calorimetry; Mechanical property; Nano composites; Nanoclays; polypropylene

Dynamic mechanical and perforation impact behavior of all-PP composites containing beta-nucleated random PP copolymer as matrix and stretched PP homopolymer tape as reinforcement: effect of draw ratio of the tape - Abraham, Thomas N.; Wanjale, S.; Siengchin, S.; Karger-Kocsis, Jozsef (Journal of Thermoplastic Composite Materials, 2011)
Cross-ply all-polypropylene (PP) composite laminates were prepared by hot consolidation after tape winding combined with film stacking. Alpha (alpha) PP tapes of different draw ratios (DR = 8 and 12), produced by online extrusion stretching, served as reinforcements. Beta (beta)-nucleated random PP copolymer, introduced in the form of a film, composed the matrix. The E-modulus of the PP tapes increased whereas their density decreased with increasing DR. The volume fraction of the reinforcement and the void content were estimated using optical microscopic images. The all-PP composites were subjected to dynamic mechanical thermal analysis, flexural, and instrumented falling weight impact tests. It was found that with increasing draw ratio of the alpha-PP tapes, the stiffness, strength, and perforation resistance of the composites were improved.
Keywords: all-polypropylene composite; draw ratio; dynamic mechanical thermal analysis; instrumented falling weight impact; polypropylene

Gamma-initiated oxidation of isotactic polypropylene: effect of gamma-dose rate on durability - Alariqi, Sameh A. S.; Singh, R. P.; Rao, B. S. M. (Arabian Journal for Science and Engineering, 2011)
The effect of gamma-irradiation dose rate on the chemical, molecular, and mechanical properties of isotactic polypropylene (iPP) films was investigated using three different Co-60 sources with dose rates of 600, 660, and 780 Gy h(-1). Fourier transform infrared spectroscopy coupled with chemical derivatization with NO and SF4, and measurements of the elongation at break, toughness, and molecular weight were used to describe the effects of gamma-dose rate on iPP. It was found that the formation of oxidation products depended significantly on the dose rate. However, the kinetic accumulation of ketones were more sensitive to the dose rate of gamma source. Degradation induced by gamma-radiation depends on the dose rate-the degradation of mechanical properties was more significant at a low dose rate than at a high dose rate. It was found that the lower the dose rate, the higher the degree of oxidation in terms of the formation of gamma-products. The mechanism of gamma-degradation is discussed based on the correlation between the changes in chemical and physical properties upon exposure to gamma-radiation.
Keywords: Chemical and physical properties; Dose rate; gamma-irradiation; polypropylene

Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Durable polymer composites preparation with oxy-delignified banana fiber for automotive parts: A study on mechanical and thermal properties - Mulla, Abdul Mannan; Munagala, Chandan K.; Kesari, Aman K.; Raju, L. Yugender; Nagar, Harsha; Behara, Dilip K.; Aniya, Vineet (INDUSTRIAL CROPS AND PRODUCTS, 2024)
Keywords: Automotive parts; Banana fiber; Oxygen delignification; polypropylene; Twin-screw extruder